Recent insights into metabolic and signalling events of directional root growth regulation and its implications for sustainable crop production systems - Retzer, Katarzyna; Weckwerth, Wolfram (Frontiers in Plant Science, 2023)
Roots are sensors evolved to simultaneously respond to manifold signals, which allow the plant to survive. Root growth responses, including the modulation of directional root growth, were shown to be differently regulated when the root is exposed to a combination of exogenous stimuli compared to an individual stress trigger. Several studies pointed especially to the impact of the negative phototropic response of roots, which interferes with the adaptation of directional root growth upon additional gravitropic, halotropic or mechanical triggers. This review will provide a general overview of known cellular, molecular and signaling mechanisms involved in directional root growth regulation upon exogenous stimuli. Furthermore, we summarize recent experimental approaches to dissect which root growth responses are regulated upon which individual trigger. Finally, we provide a general overview of how to implement the knowledge gained to improve plant breeding.